The use of wide-mesh gauze impregnated with lambda-cyhalothrin covering wall openings in huts as a vector control method in Suriname Uso de tela de malha larga impregnada com lamba-cyhalotrina como método de controle vetorial - Jaco Voorham (Universidade de São Paulo, 1997)
An alternative vector control method, using lambda-cyhalothrin impregnated wide-mesh gauze covering openings in the walls of the houses was developed in an area in the Eastern part of the interior of Suriname. Experimental hut observations showed that Anopheles darlingi greatly reduced their biting activity (99-100%) during the first 5 months after impregnation. A model assay showed high mortality both of mosquitoes repelled by the gauze as well as of those that succeeded in getting through it. A field application test in 270 huts showed good acceptance by the population and good durability of the applied gauze. After introducing the method in the entire working area, replacing DDT residual housespraying, the malaria prevalence, of 25-37% before application dropped and stabilized at between 5 and 10% within one year. The operational costs were less than those of the previously used DDT housespraying program, due to a 50% reduction in the cost of materials used. The method using widemesh gauze impregnated with lambdacyhalothrin strongly affects the behavior of An. darlingi. It is important to examine the effect of the method on malaria transmission further, since data indirectly obtained suggest substantial positive results. Foi desenvolvido, na parte oriental do interior do Suriname um método alternativo de controle antivetorial, usando uma tela de malha larga impregnada com lambda-cyhalotrina, cobrindo as aberturas das paredes das casas. Observações com casas experimentais mostraram uma redução de picadas muita alta (99%) de Anopheles darlingi durante os primeiros 5 meses após a impregnação. Um ensaio mostrou alta mortalidade dos mosquitos, repelidos ao tentar passar pelo tule, além daqueles que conseguiram passar. A aplicação no campo revelou resultados promissores deste método de controle antivetorial, boa aprovação da população e baixos custos operacionais em relação à borrifação residual com DDT.